Synthesis, characterization, electronic structure, and photocatalytic activity of nitrogen-doped TiO2 nanocatalyst - Sathish, M; Viswanathan, B; Viswanath, RP; Gopinath, Chinnakonda S. (Chemistry of Materials, 2005)
Nitrogen-doped TiO2 (N-TiO2)) nanocatalyst with spherical shape and homogeneous size has been synthesized through a chemical method using TiCl3 as precursor. The light absorption onset shifts from 380 nm on pure TiO2 to the visible region at 550 nm with N-TiO2. A clear decrease in the band gap and the nitrogen 2p states on the top of the valence band on N-TiO2 (compared to TiO2) is deduced from the optical absorption spectroscopy results. The chemical nature of N has been evolved as N-Ti-O in the anatase TiO2 lattice as identified by X-ray photoelectron spectroscopy (XPS). Photocatalytic decomposition of methylene blue has been carried out both in the UV and in the visible region and N-TiO2 shows higher activity than the Degussa P25 TiO2 photocatalyst in the visible region.

Selective ortho-methylation of phenol with methanol over copper manganese mixed-oxide spinel catalysts - Reddy, A. Satyanarayana; Gopinath, Chinnakonda S.; Chilukuri, Satyanarayana V. (Journal of Catalysis, 2006)
Methylation of phenol with methanol as an alkylating agent to produce 2,6-xylenol was investigated over copper manganese mixed oxide spinels, CuxMn3-xO4 (x = 0, 0.25, 0.5, 0.75, and 1) prepared through co-precipitation. The catalytic activity strongly depends on the composition, acid-base properties, and structural stability. Various parameters, including catalyst composition, reaction temperature, feed composition, and durability of the catalyst during methylation, were investigated. Mainly o-cresol and 2,6-xylenol, along with small amounts of mesitol, were found in the product. A high ortho-selectivity of 100%, with 2,6-xylenol selectivity of 74%, was observed over Cu0.25Mn2.75O4 at 673 K. These catalysts were investigated using various techniques, including BET surface area, XRD, DRS UV-vis, TPD of NH3 and CO2, TPR, and X-ray photoemission spectroscopy (XPS). Powder XRD of the catalysts revealed the formation of copper-manganese spinels with hausmannite (Mn3O4) tetragonal structure, for x = 0-0.5, whereas an increase in copper content (x > 0.5) led to the formation of cubic Cu1.5Mn1.5O4 phase. DRS UV-vis, and FTIR further supported the changes in structural phases observed by XRD. Temperature-programmed desorption Of CO2 and NH3 showed that the catalysts have strong basicity along with weak acidity when x = 0 and 0.25. XPS and XAES analysis revealed the presence of only Cu2+ ions in fresh sample with x = 0.25, whereas for x = 1.0, both Cu1+ and Cu2+ were observed. The deactivation of the catalysts is attributed to structural changes occurring during the reaction. Catalytic activity is correlated with structure, as well as with acid-base properties. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: 2; 6-xylenol; acidity-basicity; copper-manganese oxides; ortho-alkylation; phenol methylation; Spinels

Selective production of methoxyphenols from dihydroxybenzenes on alkali metal ion-loaded MgO - Vijayaraj, Munusamy; Gopinath, Chinnakonda S. (Journal of Catalysis, 2006)
Selective O-methylation of dihydroxybenzenes (DHBs; catechol, resorcinol, and hydroquinone) to methoxyphenols (MPs) was carried out with dimethylcarbonate on MgO and alkali metal ion (Li, K, and Cs)-loaded MgO between 523 and 603 K. Catalytic activity and product selectivity varied with respect to DHB substrates. Selectivity for O-methylated products increased with increasing basicity of alkali ions; however, K-MgO showed high and stable activity toward MPs. Selectivity for MPs obtained from three substrates increased in the following order: catechol < resorcinol < hydroquinone. The mode of interaction of substrates on the catalysts surface influenced reactivity and product selectivity. It is likely that the low reaction temperatures used (< 603 K) kinetically control and favor high MP selectivity from DHBs. Calcined and spent catalysts were characterized by XRD, surface area, SEM, thermal analysis, NMR, and XPS. XRD analysis revealed the formation of alkali oxide phases on alkali-loaded MgO. Crystallite size and surface area of the catalysts decreased after methylation reactions, except on K-MgO. TGA showed 4060 wt% coke deposition on spent catalysts. TGA in N-2 followed by air and C-13 CP-MAS NMR measurements indicated the nature of deposited carbon to be molecular species, graphite, MgCO3 and polyaromatics. XPS revealed the nature and availability of active sites on the spent catalysts, as well as the same changes with reaction conditions and correlated with catalytic activity. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: alkali-loaded MgO; dihydroxybenzene; K-MgO; methoxyphenol; MgO; O-methylation; thermal analysis; XPS

Selective mono-N-methylation of aniline substrates on Cu1-xZnxFe2O4 - Vijayaraj, Munusamy; Gopinath, Chinnakonda S. (Applied Catalysis A-General, 2007)
Selective mono-N-methylation of substituted anilines (o-, m- and p-toluidines, 2,6-xylidine, p-anisidine and p-aminoacetophenone) was carried out with methanol as methylating agent under vapor phase reaction conditions on Cu1-xZnxFe2O4 systems. The catalytic reactions with each aniline substrate were carried out at optimum reaction conditions (MeOH:anilines:water = 3: 1: 1, space velocity = 3.58 h(-1)) between 543 and 603 K. The presence of a ring-directing group did not have any significant influence on the N-methylaniline(s) selectivity, which remains very high; the same initial conversion/yield was observed for at least 11 h. Electronic effects due to different groups in the above aniline substrates influence the reactivity of the substrates in terms of conversion and yield. Toluidine reactivity varies with respect to the position (ortho, meta and para) of the methyl group on the phenyl ring. Para-substituted anilines (p-toluidine and p-anisidine) exhibit comparable catalytic activity, while p-aminoacetophenone shows higher conversion. The perpendicular orientation of toluidine substrates on catalyst surfaces influences the conversion and N-methyltoluidine yield. Increased crowding at ortho-position and hence steric hindrance (aniline > o-toluidine > 2,6-xylidine) restrict the substrates interaction with the catalyst surface, and 2,6-xylidine shows no reactivity. The best catalytic activity observed with Cu0.5Zn0.5Fe2O4 was due to a heterogeneous distribution of metal ions on the surface with Zn serving as active spacer group as well as methyl species source. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: mono-N-methylation; N-methylaniline; N-methylation; selective N-methvlation; spinel

Structure, electronic structure, optical, and dehydrogenation catalytic study of (Zn1-zInz)(O1-xNx) solid solution - Mapa, Maitri; Sivaranjani, Kumarsrinivasan; Bhange, Deu S.; Saha, Biswajit; Chakraborty, Purushottam; Viswanath, Annamraju Kasi; Gopinath, Chinnakonda S. (Chemistry of Materials, 2010)
Indium and nitrogen codoping in ZnO leads to a solid solution of InN in ZnO with I composition of(Zn1-zInz)(O1-xNx). A simple solution combustion method has been adopted to prepare the above materials in less than 10 min with metal nitrates as the metal loll source and urea as fuel. With reference to ZnO, significant increase in lattice parameters was observed with increasing In-content. However, the In2O3 phase was Observed along with InN for]it content >= 10%. Optical absorption extended into the Visible region, at least LIP to 550 nm, demonstrates an effective reduction of optical band gap due to the formation of solid Solution. A new feature observed just above O2p valence band in X-ray photoelectron spectroscopy (XPS) suggests the creation of N 2p states from InN; the N Is core level XPS result too confirms nitride contribution. Raman spectroscopy and secondary ion mass spectrometry results show direct In-N, Zn-N. and In-N-Zn fragments in (Zn1-zInz)(O1-x,N-x). Catalytic activity explored for Oxidation of 2-butanol to ethyl methyl ketone demonstrates a high selectivity at 350 and 400 degrees C. All of the above characteristics suggest the multifunctional nature of (Zn1-zInz)(O1-xNx) and its potential for other applications.

Selective hydrogenation of chloronitrobenzenes with an MCM-41 supported platinum allyl complex derived catalyst - Indra, Arindam; Rajamohanan, Pattuparambil R.; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Applied Catalysis A-General, 2011)
A platinuin precatalyst (1) has been prepared by reacting [(eta(3)-C3H5)(4)Pt4Cl4] with surface functionalized MCM-41 with pendant -(CH2)(3)NH(CH2)(2)NH2 groups. For the hydrogenation of o-, m- and p-chloronitrobenzenes to the corresponding chloroanilines, 1 is found to be a highly active catalyst with good selectivities for them-and p-isomers. Its performance is superior to that of its palladium analogue and far superior to that of commercial (5%) Pt/C or (5%) Pt/Al2O3. Comparison of solid state and solution NMR data and other evidences indicate that on treatment with the functionalized MCM-41 support; [(eta(3)-C3H5)(4)Pt4Cl4] loses the ally! ligand. XPS data show that in the fresh catalyst Pt is present in the 2+ oxidation state. Based on these and analytical data, co-ordination by surface diamine and hydroxo groups to Pt2+ in 1 is suggested. In the used catalyst both Pt2+ and Pt are present but the amount of metallic platinum is similar to 16% of the total. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chloronitrobenzenes; Dehydrohalogenation; heterogeneous catalyst; MCM-41; Selective hydrogenation

Simple one pot synthesis of nano gold-mesoporous silica and its oxidation catalysis - Sekhar, A. C. Sunil; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S.; Vinod, C. P. (Catalysis Today, 2012)
A simple one pot synthesis strategy using a non ionic triblock copolymer P123 as reducing as well as templating agent has been employed to prepare nano gold particles incorporated in the pores of mesoporous silica catalyst. The catalyst is characterized by XRD, nitrogen adsorption desorption isotherms at 77 K and TEM. The presence of small gold nanopartilces (similar to 2-4 nm) clearly demonstrated that this strategy can be effective in incorporating Au inside mesochannels. The catalyst reduced at 300 degrees C in H-2 was found to be active for oxidation reactions, such as CO oxidation, and benzyl alcohol. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Alcohol oxidation; CO oxidation; Gold catalysis; Mesoporous silica

Synthesis and catalytic activity of monodisperse gold-mesoporous silica core-shell nanocatalysts - Sekhar, A. C. Sunil; Meera, C. J.; Kottavarithottil Ziyad; Gopinath, Chinnakonda S.; Vinod, C. P. (Catalysis Science & Technology, 2013)
Core-shell nanostructures, where gold nanoparticles of sub 10 nm size are successfully encapsulated inside porous silica spheres, have been prepared. The detailed characterization of the catalyst shows a high surface area and good mesoporosity. The sinter resistance of the catalyst under repeated cycles of the CO oxidation reaction is observed.

Solid-state NMR investigations of a MgCl2 center dot 4(CH3)(2)CHCH2OH molecular adduct: a peculiar case of reversible equilibrium between two phases - Thushara, K. S.; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Gopinath, Chinnakonda S. (Journal of Physical Chemistry A, 2014)
MgCl2 center dot xROH molecular adducts are extensively employed as a support material for Ziegler-Natta polyolefin catalysis. However, their structural properties are not well understood. Recently, we reported on the preparation of an isobutanol adduct, MgCl2 center dot 4(CH3)(2)CHCH2OH (MgiBuOH) (Dalton Trans. 2012, 41, 11311), which is very sensitive to the preparation conditions, such as the temperature and refluxing time. For the present study, the structural properties of MgiBuOH adducts prepared under different conditions have been investigated thoroughly by solid-state NMR and nonambient XRD. Formation of two phases has been confirmed, and in situ variable temperature solid-state NMR measurements confirm the coexistence of two phases as well as the oscillation from one to another phase. It is expected that such molecular adducts could have a significant role in organic transformation reactions due to an oscillating structural component. An understanding of phase oscillation with the Mg2+ ion as the central metal ion might shed some light toward understanding various biological and structural functions.

Structural investigations of porous MgCl2-2-butanol molecular adduct as support for olefin polymerization - Thushara, K. S.; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Gopinath, Chinnakonda S. (Applied Catalysis A-General, 2014)
A new heterogeneous Ziegler-Natta (Z-N) catalyst support material, MgCl2 center dot 4(CH3CH(OH)CH2CH3) (Mg2BuOH) has been synthesized. 2-Butanol, a linear, secondary alcohol was chosen for the generation of an active MgCl2 support which results in a Z-N catalyst with TiCl4. Significant feature of this work is the formation of rod shaped molecular adduct with highly porous character. Adduct material is characterized by XRD, TG-DTA, Raman spectroscopy, solid-state NMR and SEM. Activity of the Z-N catalyst supported on Mg2BuOH for ethylene polymerization is comparable with that of commercially available heterogeneous Z-N catalyst. However, there is scope to improve the activity by optimizing textural properties. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: heterogeneous catalysis; MgCl2; Molecular adduct; NMR; Polyolefin; Ziegler-Natta catalyst

SBA-15-oxynitrides as a solid-base catalyst: effect of nitridation temperature on catalytic activity - Singh, Baljeet; Mote, Kaustubh R.; Gopinath, Chinnakonda S.; Madhu, Perunthiruthy K.; Polshettiwar, Vivek (Angewandte Chemie-International Edition, 2015)
Solid bases, such as SBA-15-oxynitrides, have attracted considerable interest for potential applications as catalysts in important industrial processes. Reported herein is that by simply tuning the temperature of nitridation (ammonolysis), the catalytic activity of these solid bases can be enhanced. Solid-state NMR spectroscopy and XPS studies provided the reasoning behind this change in activity.
Keywords: heterogeneous catalysis; Nanostructures; NMR spectroscopy; photoelectron spectroscopy; solid-state structures

Seeding of Au on CdSe/CdS nanoplates using Langmuir-Blodgett technique - Das, Subhasis; Satpati, Biswarup; Chauhan, Himani; Deka, Sasanka; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (RSC Advances, 2016)
Oleyl amine capped CdSe/CdS nanoplates were synthesized by hot injection technique which formed a stable monolayer over both a water subphase and an aqueous HAuCl4 subphase using a Langmuir-Blodgett trough. Au islands were generated at the edge as well as on one specific surface of the flat nanoplates by exploiting the reducing capacity of oleyl amine to form Au nanoseeds from AuCl4- ions. The initial Au nanoseeds changed to a shell surrounding these nanoplates on prolonged exposure to the subphase containing the Au precursor. Monolayer of the hybrid structures was deposited onto suitable substrates for characterization by a number of different techniques and to study the photocatalytic activity. The same substrate with the monolayers could be re-used in several cycles of photocatalysis.

Study on doped heterojunctions in TiO2 nanotubes: an efficient photocatalyst for solar water splitting - Preethi, L. K.; Antony, Rajini P.; Mathews, Tom; Walczak, Lukasz; Gopinath, Chinnakonda S. (Scientific Reports, 2017)
The two important factors that affect sunlight assisted water splitting ability of TiO2 are its charge recombination and large band gap. We report the first demonstration of nitrogen doped triphase (anatase-rutile-brookite) TiO2 nanotubes as sun light active photocatalyst for water splitting with high quantum efficiency. Nitrogen doped triphase TiO2 nanotubes, corresponding to different nitrogen concentrations, are synthesized electrochemically. Increase in nitrogen concentration in triphase TiO2 nanotubes is found to induce brookite to anatase phase transformation. The variation in density of intra-band states (Ti3+ and N 2p states) with increase in nitrogen doping are found to be critical in tuning the photocatalytic activity of TiO2 nanotubes. The presence of bulk heterojunctions in single nanotube of different nitrogen doped TiO2 samples is confirmed from HRTEM analysis. The most active nitrogen doped triphase TiO2 nanotubes are found to be 12 times efficient compared to pristine triphase TiO2, for solar hydrogen generation. The band alignment and charge transfer pathways in nitrogen doped TiO2 with triphase heterojunctions are delineated. Bulk heterojunctions among the three phases present in the nanotubes with intra-band defect states is shown to enhance the photocatalytic activity tremendously. Our study also confirms the theory that three phase system is efficient in photocatalysis compared to two phase system.

Silicon oxidation by NAPPES: From dangling bonds to oxygen islands to 2D SiOx layer to the onset of bulk SiO2 formation - Ghosalya, Manoj Kumar; Jain, Ruchi; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2018)
Valence band and core level photoelectron spectral measurements at near-ambient pressures (NAP; up to 0.5 mbar) were made in the presence of molecular oxygen to explore the various oxidation stages of silicon surfaces. Dangling bonds feature observed on clean Si-surfaces in the valence band at ultrahigh vacuum decreases dramatically due to oxygen adsorption between ambient temperature and up to 400 K at 0.1 mbar of O-2 pressure. The adsorption of oxygen on dangling bonds appears to be localized as islands; this reflects in the surface heterogeneous character and also responsible for the broadening in the oxygen gas phase vibrational features. This is further supported by an increase in the work function and can be correlated to the presence of Hofer (molecular) precursor. When the temperature was increased to 500 K, molecular precursor species dissociates to form Si-=-0 species. This is fully supported by the change in the Si work function as well as from the observation of oxidized Si species from Si 2p core level spectra. At >= 600 K, the Si-=-0 species dissociates to form a uniform 2D oxide layer on the silicon surface, which is characterized by the reappearance of sharp vibration features for gas-phase O-2 molecules. This layer is also quite stable up to 800 K and without any further oxidation in the bulk. On increasing the temperature to 850 K at 0.2 mbar oxygen pressure, bulk Si oxidation begins and the work function increases drastically by 1 eV. An angle-dependent Si 2p spectra recorded map out the presence of elemental Si to Si4+ from bulk to the surface, respectively. A simple model is proposed to show the various stage of silicon oxidation. A continuous change in the work function and electronic states observed due to gas-lattice (O-2-Si) interaction indicates the implications for surface-dependent phenomena, such as heterogeneous catalysis, electrochemistry, 2D layered materials.

Subtle interaction between Ag and O 2 : a near ambient pressure UV photoelectron spectroscopy (NAP-UPS) investigations - Ghosalya, Manoj Kumar (Journal of Chemical Sciences, 2018)
The Ag-O2 interaction, which is at the center-stage of Ag-catalyzed partial oxidation reactions, is studied with NAP-UPS up to 0.2 mbar O2 pressure between 295 and 550 K. Three temperature regimes were identified for distinct Ag-O2 interaction, which are (a) 295–390 K, where mainly dissociative chemisorption of O2 happens, (b) 390–450 K, where diffusion of O-atoms into the sub-surfaces of Ag is prominent, and (c) >450 K, where metastable oxide forms on polycrystalline Ag surfaces. The work function (WF) of Ag changed from 4.95 (≤390 K) to 5.30 eV (390–450 K), and then to 5.7 eV (≥450 K) at 0.1 mbar O2 pressure. Oxygen population in the sub-surfaces imparts crucial modifications to Ag at 390–450 K; it makes the surface to be electron-deficient that relates to the change in the WF of Ag and facilitates the formation of space charge layer on Ag surface. Oxygen adsorbed on such modified Ag-surfaces is electrophilic in nature, and this appears at a higher binding energy in core level XPS than the chemisorbed oxygen on metallic Ag. This is supported by angle-dependent NAP-XPS studies. The subsurface population of oxygen in Ag no longer persists at >410 K when the O2 supply is removed. A high ratio of antibonding/bonding O 2p bands suggests the unique silver-oxygen interaction under the measurement conditions.
Keywords: Electronic Structure; epoxidation; heterogeneous catalysis; Surface Science

Surfactant free synthesis of Au@Ni core-shell nanochains in aqueous medium as efficient transfer hydrogenation catalyst - Vysakh, A. B.; Shebin, K. J.; Jain, Ruchi; Sumanta, P.; Gopinath, Chinnakonda S.; Vinod, C. P. (Applied Catalysis A-General, 2019)
A surfactant free aqueous phase synthesis method is reported for the generation of highly lattice mismatched Au@Ni core-shell nanochains without using any expensive and hazardous organic ligands. As synthesised Au@Ni nanochain structures showed high thermal stability and bulk oxidation resistance up to 300 degrees C. In situ near ambient pressure XPS (NAPXPS) analysis has been done for the bare Au@Ni nanochain surfaces under oxygen atmosphere and at different temperatures which showed evidence for the surface oxidation resistance of naked Au@Ni nanochains up to 200 degrees C. Ligand or capping agent free Au@Ni nanochain surfaces are found to be highly active for transfer hydrogenation of acetophenone to 1-phenyl ethanol an important commodity in perfumery industry.
Keywords: Au@Ni nanochains; core-shell; NAPXPS; Surfactant free; synergistic effects; transfer hydrogenation

Scalable and thin film approach for solar hydrogen generation: a review on enhanced photocatalytic water splitting - Gopinath, Chinnakonda S.; Nalajala, Naresh (Journal of Materials Chemistry A, 2021)
Although nearly five decades of efforts have gone into solar water splitting (SWS), still success eludes and there is no big breakthrough till date. While huge importance is given either individually or concurrently to the three fundamental steps, namely, light absorption, charge carrier separation and diffusion and charge utilization at redox sites, many aspects that are practically helpful to improve the efficiency are not widely discussed and practised. Nonetheless, by adopting a number of small, but significant changes, solar hydrogen production can be enhanced. The present review discusses such different approaches employed for photocatalytic water splitting reported in the literature. For example, an increase of up to two orders of magnitude in solar hydrogen generation was observed with a film form compared to the particulate form of the same catalyst. Discussion on various approaches of enhanced hydrogen production under sunlight and one sun conditions is the main focus of this review, in particular with thin-film forms. The merits and demerits of thin film and particulate methods, respectively, are addressed in detail. Potential methods and successful stories on scalability are also discussed in the present review. In contrast to charge collection over a long distance in solar cell-based methods, a film-based method discussed shows that the local charge utilisation at a zero applied potential is an attractive feature for SWS. A comparison is provided between the PEC-WS and SWS for solar hydrogen generation, and how far we are from the reality to produce solar hydrogen on an industrial scale. We believe the presently practised diverse evaluation efforts may be truncated to fewer methods such as film-based evaluation and in a focussed manner to tackle the SWS issue towards sustainable production of solar hydrogen.

Sulfur functionalization via epoxide ring opening on a reduced graphene oxide surface to form metal (II) Organo-bis-[1,2]-oxathiin - Kumar, Praveen; Bajpai, Himanshu; Gopinath, Chinnakonda S.; Luwang, Meitram Niraj (Inorganic Chemistry, 2022)
The epoxide ring-opening reaction in graphene oxide (GO) by nucleophiles is a very fascinating and advanced methodology to develop novel functional material. Herewith, we report an advanced strategy for opening the epoxide ring on the rGO surface via easily an available nucleophile (Na2S), which is further functionalized with O atom to obtain four-membered rings (FMRs). The Cd coordination with the S atom puts extra stress on the FMR leading to the C-C bond cleavage of the four-membered heteroatomic rings on the rGO surface. This strategic approach leads to the fabrication of an innovative metal organo-bis-[1,2]-oxathiin (MOBOT) chemical moiety (M = Cd, Zn). The MOBOT compound further shows enhanced H-2 generation activity and hence is promising as a potential photocatalyst for solar hydrogen generation. This compound might also be a potential candidate for optoelectronic applications.

Sustainable CO2 reduction on in (2)O(3 )with exclusive CO selectivity: catalysis and in situ valence band photoelectron spectral investigations - Mhamane, Nitin B.; Chetry, Sibo; Ranjan, Ravi; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2022)
This study demonstrates a sustainable catalytic CO2 conversion to near 100% CO selectivity at ambient pressure on In2O3. Critically, high CO yield could be observed at the cost of undesired methanation, using a lower than stoichiometric amount of hydrogen in the feed; 1:1 and 1:0.67 CO2:H-2 ratios exhibit 98-99.6% CO selectivity with 25-38% CO2 conversion between 773 and 873 K. CO2 and H-2 conversion under steady-state conditions at 773-873 K suggests a 1:1 ratio of adsorbed reactants (with 1:0.67 CO2:H-2 feed) on the catalyst surface, underscoring the presence of an ideal reactant composition for the reverse water-gas shift reaction, while H-2-rich feed compositions show the H-2-dominated surface. Surface electronic structure changes, under near-operating conditions, were explored with near ambient pressure photoelectron spectroscopy (NAPPES), and the interesting findings are as follows: (a) A shift in the valence band to lower binding energy, up to 0.6 eV, was observed because of electron filling at high temperatures. (b) An observation of heterogeneous nature of the catalyst surface under NAPPES measurement conditions is attributed to the generation of active oxygen vacancy (O-v) sites, which in turn changes the work function of In2O3. (c) The above changes are found to be reversible, when the reaction was stopped. Vibrational features of the reactant molecules were observed to be broadened in the active temperature window of the catalyst supporting the heterogeneous character of the catalyst surface because of dynamic O-v generation. By optimizing gas hourly space velocity, CO2:H-2 ratio, and reaction temperature, exclusive CO selectivity is possible with a H-2:CO2 ratio of similar to 0.67, which will avoid the product separation stage altogether, while minimizing the expensive H-2 in the reactant feed.
Keywords: heterogeneous catalysis; Oxygen vacancy; photoelectron spectroscopy; RWGS; Work function

Selective and generic photocatalytic oxidation of alcohol with Pd-TiO2 thin films: butanols to butanal/butanone with different morphologies of Pd and 0.5 theta(Pt)-Pd counterparts - Salgaonkar, Kranti N.; Kale, Sandip R.; Nalajala, Naresh; Mansuri, Sayana; Gopinath, Chinnakonda S. (Chemistry-An Asian Journal, 2023)
The present study reports on the photocatalytic oxidation of butanols to butanal/butanone using thin film form of facet-dependent nano-Pd supported on commercial TiO2 under one-sun condition and demonstrates the generic nature. Pd-nanocube (Pd-NC(100)), Pd-truncated octahedron (Pd-TO (100) and (111)), polycrystalline (Pd-PC), and their counterparts with half-a-monolayer Pt-coated on Pd (0.5 theta(Pt)-Pd)) have been used as co-catalyst. A potentially scalable thin film form of Pd/TiO2 photocatalyst, prepared by drop-casting method, has been employed to study oxidation of n-butanol, 2-butanol, and iso-butanol to corresponding aldehyde/ketone. 100% selectivity is demonstrated to respective aldehyde/ketone with any catalyst used in the present study with varying degree of butanols conversion by NMR. 0.5 theta(Pt)-Pd-TO/TiO2 shows the highest conversion of 2-butanol to butanone (13.6% in 4 h). Continuous 10 h of reaction with the most active 0.5 theta(Pt)-Pd-TO/P25 catalyst demonstrates 31% conversion of 2-butanol to butanone, and catalyst recyclability has been demonstrated. The present protocol can be scalable to large scales to maximize the conversion in direct sunlight. Due to its generic nature, the current method can also be applied to many other alcohols and substrate molecules.
Keywords: energy conversion; Nanomaterials; Oxidation; Photocatalysis; Sustainability

Selective anodic transformation of glycerol with ZnCo 2 O 4 2D nanoplates: sustainable coproduction of carbon-negative green hydrogen and formic acid - Saha, Arindam; Murugiah, Vasantharadevi; Kollenteakathootu, Jayalakshmi; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2025)
In the pursuit of sustainable green hydrogen production, the electrooxidation of abundantly available carbon-containing molecules at a significantly low voltage presents a promising pathway, helping to reduce the cost of hydrogen generation while simultaneously yielding value-added chemicals/fuels. In the current study, we report the template-free green synthesis of ZnCo2O4 directly on Ni-foam (NF), demonstrating anodic stability and bifunctional electrocatalytic activity toward alkaline (1 M KOH) glycerol oxidation over an extended duration of 230 h at 50 mA cm- 2. The catalyst's high electrochemical surface area contributes to its remarkable performance, enabling sustained high current density. Compared with monometallic (ZnO or Co3O4) oxides, ZnCo2O4 oxide reveals superior catalytic performance. The two-electrode electrolyzer setup (ZnCo2O4 oxide/NF || ZnCo2O4 oxide/NF) operates at a significantly low cell potential of 1.9 V to achieve 100 mA cm- 2 in 0.2 M glycerol, which is 180 mV lower than that of conventional 1 M KOH solution. The three-electrode setup achieved 1 A/cm2 current density at 1.907 V vs RHE. Both anodic and cathodic processes exhibit high Faradaic efficiency, achieving 98% efficiency for H2 and 90% selectivity toward formate generation, along with significant methanol production. This demonstrates efficient C-C bond cleavage capability with glycerol to predominantly C1-products. The electrocatalytic formate production from alkaline glycerol using ZnCo2O4 offers an energy-efficient pathway, facilitating carbon-negative green hydrogen generation, thus contributing to a cleaner and sustainable energy landscape.
Keywords: energy conversion; Formic acid; glyceroloxidation; green H-2; water electrolysis

Synthesis of Pd-integrated carbon Dot@TiO2 thin film for photocatalytic glycerol reforming reaction for producing hydrogen - Abraham, Athira; Salgaonkar, Kranti N.; Nivedhitha, Thazhath R.; Ekal, Vishal Ashok; Kondhekar, Deepali; Chakraborty, Shubhankar; Gopinath, Chinnakonda S.; Saha, Avishek (Chemistry-an Asian Journal, 2025)
A series of thin-film photocatalysts comprising TiO2 modified with carbon dots (CDs) dispersed either with palladium (Pd-CD/TiO2) or nickel (Ni-CD/TiO2) were synthesized via solid-state and wet-impregnation methods. Morphological characterization (HR-TEM, SEM-EDS) confirmed the anatase phase of TiO2 and the atomic dispersion of metal-integrated CDs on its surface. UV-vis DRS and XPS analyses revealed a marginal red shift in band-gap and the presence of sp2-hybridized graphitic carbon, and metal-carbon interactions, indicating enhanced light absorption and charge separation through Schottky junctions. Under direct sunlight illumination, Pd-CD/TiO2 thin film exhibited superior hydrogen yield (1167 mu mol g-1 h-1) and maintained stability over 25 h, outperforming Ni-CD/TiO2 (494 mu mol g-1 h-1) and bare TiO2 (166 mu mol g-1 h-1) photocatalyst thin films. Concurrent glycerol oxidation at neutral pH (pH similar to 7) yields glycolaldehyde (41% selectivity), formic acid, and dihydroxyacetone as value-added products. Enhanced photocurrent density and lower impedance of Pd-CD/TiO2 corroborate improved charge carrier separation and dynamics. The results demonstrate that Pd-CD synergistically improves the photocatalytic performance of the Pd-CD/TiO2 for sustainable hydrogen generation and selective biomass valorization.
Keywords: Glycerol oxidation; Graphitic carbon dots; hydrogen production; Photocatalysis; titania